Comparison of photocatalytic and transport properties of TiO2 and ZnO nanostructures for solar-driven water splitting1. Issue 12 (28th March 2015) - Hernández, Simelys; Hidalgo, Diana; Sacco, Adriano; Chiodoni, Angelica; Lamberti, Andrea; Cauda, Valentina; Tresso, Elena; Saracco, Guido
<x xml:space="preserve">Abstract</x> Water splitting interfacial reaction kinetics and charge transport of four TiO2- and ZnO-based nanostructures with similar thickness are investigated.